DIGITAL COMMUNICATIONS - Proakis John G (Mcgraw Hill, 2001)
PROBABILITY AND STOCHASTIC PROCESSES SOURCE CODING CHARACTERIZATION OF COMMUNICATION SIGNALS AND SYSTEMS
PROBABILITY AND STOCHASTIC PROCESSES SOURCE CODING CHARACTERIZATION OF COMMUNICATION SIGNALS AND SYSTEMS